PERANCANGAN SISTEM INFORMASI MANAJEMEN KEGIATAN KEPEMUDAAN BERBASIS PHP MYSQL DI DINAS PEMUDA DAN OLAHRAGA KABUPATEN BANYUWANGI - Ria Nufika; Ahmad Homaidi; Yusfi Chusnul Raufah (Jurnal Riset Teknik Komputer, 2025)
The Youth and Sports Office of Banyuwangi Regency plays an important role in managing various youth programs, but the process of recording, reporting, and data collection is still carried out manually, resulting in inefficiency and inaccuracy of information. This study aims to design a web-based youth activity management information system using PHP and MySQL that can manage activity data, participants, and reports in an integrated manner. The method used is a qualitative descriptive approach with data collection techniques through observation, interviews, and literature studies, as well as a system design method using the Waterfall model. The designed system provides features such as participant registration, activity data input, documentation management, and reporting. The design results show that this system can improve administrative efficiency, facilitate the evaluation process, and support transparency in youth data management at the Banyuwangi Youth and Sports Office.